EXPLORING MULTIMEDIA-ASSISTED PRACTICES FOR EDUCATORS’ PROFESSIONAL DEVELOPMENT IN ENGLISH LANGUAGE TEACHING IN RURAL HIGHER INSTITUTIONS IN CHINA - Xin Zhang (PUPIL: International Journal of Teaching, Education and Learning, 2026)
The digital transformation of higher education has increased expectations for English as a Foreign Language (EFL) educators to engage in technology-assisted professional development (PD). In rural higher education institutions in China, however, multimedia-assisted PD is often constrained by limited infrastructure, fragmented training opportunities, and institutional support. This study examines how rural EFL educators perceive, use, and adapt multimedia-assisted practices for professional development. Using a pragmatic mixed-methods design, the study integrates questionnaire data from 303 educators with semi-structured interview data. The findings show high perceived need and value with persistent structural and multimedia-specific barriers. Qualitative evidence further indicates that educators respond through adaptive and peer-supported practices, including selective resource use, pedagogical recontextualization, and informal learning networks. Based on the integrated findings, the study proposes a context-sensitive support-constraint framework that explains how institutional conditions and teacher agency interact to shape multimedia-assisted PD. The study contributes empirical insights for ELT teacher development in rural higher education environment.